An experimental study validating the conditions necessary to prevent the formation and ingestion of aero-inlet vortices - Omar Faruq Idris (2014)
The race to create aircraft engines that push the boundaries of efficiency leads to the creation of engines that are not only larger in size, but have lower ground clearances as well. Under certain flow conditions, a surface to inlet vortex may form. These vortices could potentially damage the engine through increased instability, wear and even compressor stall. However, the most damaging effect is the ingestion of foreign objects that are lifted by these vortices.